2022
DOI: 10.3389/fbioe.2022.889291
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Drug Delivery Systems for Induction of Tolerance and Treatment of Autoimmune Diseases

Abstract: Autoimmune disease is a chronic inflammatory disease caused by disorders of immune regulation. Antigen-specific immunotherapy has the potential to inhibit the autoreactivity of inflammatory T cells and induce antigen-specific immune suppression without impairing normal immune function, offering an ideal strategy for autoimmune disease treatment. Tolerogenic dendritic cells (Tol DCs) with immunoregulatory functions play important roles in inducing immune tolerance. However, the effective generation of tolerogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 172 publications
(232 reference statements)
1
11
0
Order By: Relevance
“…The evaluation of metformin release from nanoMIL-89 at different time points revealed a successful and controlled release, reaching approximately 100 µg/ml at 96 hours. This gradual release pattern is crucial in evading premature drug deactivation by the immune system, preventing rapid immune tolerance, and ensuring sustained therapeutic e cacy [40]. These ndings align with a previous study on nanoMIL-89, which demonstrated its ability to circulate, and release loaded drugs in plasma for up to 4 days [27], potentially addressing metformin's short plasma half-life [31,32].…”
Section: Discussionsupporting
confidence: 84%
“…The evaluation of metformin release from nanoMIL-89 at different time points revealed a successful and controlled release, reaching approximately 100 µg/ml at 96 hours. This gradual release pattern is crucial in evading premature drug deactivation by the immune system, preventing rapid immune tolerance, and ensuring sustained therapeutic e cacy [40]. These ndings align with a previous study on nanoMIL-89, which demonstrated its ability to circulate, and release loaded drugs in plasma for up to 4 days [27], potentially addressing metformin's short plasma half-life [31,32].…”
Section: Discussionsupporting
confidence: 84%
“…A recent approach for targeted treatment of RA involves delivery of RA-associated antibodies and antigens to auto-reactive lymphocytes or dendritic cells, with the aim of inducing antigen-specific immune tolerance [178] while maintaining protective immunity [179,180]. To this end, future work should explore as many RA-associated antibodies and antigens as possible.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Less attention has been paid to the other side of the immune balance, the potential use of MNPs for the magnetic targeting of immunosuppressive cells (tolDCs, iTregs…) towards lymphoid tissues as a strategy to improve cell-based immunotherapies in autoimmune contexts. What has been studied extensively is the interaction between DCs and different types of NPs [ 190 , 191 , 192 ], as well as the specific use of nanomaterials to induce the polarization of DCs towards tolDCs in vivo as a therapeutic approach for autoimmune pathologies [ 193 , 194 ]. What lessons can be learned from these studies to extend the idea of magnetic targeting to tolDCs?…”
Section: Nanobiomedicinementioning
confidence: 99%